Identification of Morphological Characteristic of Dragon Fruit (Hylocereus sp.) in Sitinjo District of Dairi Regency North Sumatera - Nina Unzila Angkat; Luthfi Azis Mahmud Siregar; Revandy Iskandar Damanik (Jurnal Agroekoteknologi, 2018)
This reserach aimed to identify the morphological chracteristics and phylogenetic relationship of Dragon Fruit (Hylocereus sp.) plants. The research was started from April 2017 until May 2017 at Sitinjo district of  Dairi Regency North Sumatera with survey methode using dragon fruit descriptor of Hylocereus by International Union For The Protection Of New Varieties (UPOV). Sampling technique using purposive sampling. Exploration results was obtained 24 genotypes of Dragon Fruit plants based on identified fruit morphological characteristic. Based on clustering analyze the closest genetic relationship is on genotype G17 and G23 which has 2 differences of 7 characteristic with dissimilarity coeficient is 1,000 and the furthest genetic relationship is on genotype G18 and G26 with dissimilarity coeficien is 4,796 which has 5 differences of 7 characteristic.